Estrategias de marketing digital y su incidencia en la competitividad de las empresas de transporte interprovincial del cantón Quevedo, año 2023 - Vera Sánchez, Ariana Andreina (2024)
The present investigation was developed in the Quevedo canton, in interprovincial land transportation companies. It addresses a very important problem such as the impact of digital marketing strategies on their competitiveness. Its objective is to analyze the applied strategies of digital marketing and its impact on the competitiveness of the interprovincial land transport companies under study. In the execution process, the inhabitants of the Quevedo canton were chosen as a sample of the market surveys of interprovincial land transportation companies. The research was qualitative and quantitative. Deductive, inductive and analytical methods were used. The Research allowed us to determine that the adoption and use of digital marketing strategies by interprovincial transport companies have little positioning in social networks and those that have web pages do not have attractive portals that allow interaction with their users, on the other hand. , the perception of customers about the effectiveness of digital marketing has a significant impact on the quality of service and competitiveness, customers value that the transport units are in good condition and are comfortable, and that their digital pages have interactive and useful information, finally digital strategies have an impact on key competitiveness factors, among the most suggested are online ticket sales and online reservations.